Research on trajectory tracking control of manipulator based on modified terminal sliding mode with double power reaching law. (14th May 2019) - Xia, Yan; Xie, Wei; Ma, Jiachen
This article proposes a control strategy that combines the double power reaching law with the modified terminal sliding mode for tracking tasks of rigid robotic manipulators quickly and accurately. As a significant novelty, double power reaching law can reach the sliding surface in finite time when the system is in any initial state. At the same time, modified terminal sliding surface guarantees the system that position and velocity error converge to be zero approximately. In other words, the control law is able to make the system slip to the equilibrium point in a finite time and improves the speed of the system approaching and sliding modes. The simulation results demonstrate the practical implementation of the control strategy, verify its robustness of more accurate tracking and faster disturbance rejection, and weaken the chattering phenomenon more effectively compared with the conventional terminal sliding mode controller.